Exploring healthcare-seeking behavior of most vulnerable groups amid the COVID-19 pandemic in the humanitarian context in Cox's Bazar, Bangladesh: Findings from an exploratory qualitative study. - Muhammad Riaz Hossain; Ateeb Ahmad Parray; Rafia Sultana; Bachera Aktar; Sabina Faiz Rashid (Public Library of Science (PLoS), 2023)
The COVID-19 pandemic has raised new concerns about healthcare service availability, accessibility, and affordability in complex humanitarian settings where heterogeneous populations reside, such as Rohingya refugees in Bangladesh. This study was conducted in ten Rohingya camps and four wards of the adjacent host communities in Cox's Bazar to understand the factors influencing healthcare-seeking behavior of the most vulnerable groups (MVGs) during COVID-19 pandemic. Data were extracted from 48 in-depth interviews (24 in each community) conducted from November 2020 to March 2021 with pregnant and lactating mothers, adolescent boys and girls, persons with disabilities, elderly people, and single female-household heads. This study adopted Andersen's behavioral model of healthcare-seeking for data analysis. Findings suggest that the healthcare-seeking behavior of the participants amid COVID-19 pandemic in the humanitarian context of Cox's Bazar was influenced by several factors ranging from socioeconomic and demographic, existing gender, cultural and social norms, health beliefs, and various institutional factors. Lack of household-level support, reduced number of healthcare providers at health facilities, and movement restrictions at community level hampered the ability of many participants to seek healthcare services in both Rohingya and host communities. Most of the female participants from both communities required permission and money from their male family members to visit healthcare facilities resulting in less access to healthcare. In both communities, the fear of contracting COVID-19 from healthcare facilities disproportionately affected pregnant mothers, elderly people, and persons with disabilities accessing health services. Additionally, the economic uncertainty had a significant impact on the host communities' ability to pay for healthcare costs. These findings have the potential to influence policies and programs that can improve pandemic preparedness and health system resilience in humanitarian contexts.